PENERAPAN MODEL VISUALIZATION, AUDITORY, KINESTETHIC DENGAN MEDIA AUDIO VISUAL DALAM PENINGKATAN HASIL BELAJAR IPS PADA SISWA KELAS IV SDN 4 KUTOSARI TAHUN AJARAN 2015/2016. - SUKRON, MUHAMMAD (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Visualization, Auditory, Kinestetic model using Audio Visual Media in Improving Social Science Learning for the Fourth Grade Students of SD Negeri IV Kutosari in the Academic Year of 2015/2016.The objectives of this research is to improve social science learning about the development of technology. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were 44 students of the fourth grade of SD Negeri 4 Kutosari. The conclusion of this research is the application of VAK model using audio visual media can improve social science learning for the fourth grade students of SD Negeri IV Kutosari.Keywords: Visualization, Auditory, Kinestethic model, audio visual media, social science learningAbstrak: Penerapan  Model Visualization, Auditory, Kinestethic dengan  Media Audio Visual  Dalam Peningkatan Hasil Belajar IPS pada Siswa Kelas IV SDN 4 Kutosari Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan hasil belajar IPS tentang perkembangan teknologi, dan Penelitian ini merupakan penelitian kolaborasi yang dilakukan selama 3 siklus. Subjek penelitian ini adalah siswa kelas IV SDN 4 Kutosari berjumlah 44 siswa. Kesimpulan penelitian ini adalah penerapan Penerapan  Model Visualization, Auditory, Kinestethic dengan  Media Audio Visual dapat meningkatkan hasil belajar IPS pada siswa kelas IV SDN 4 Kutosari.Kata Kunci: Model Visualization, Auditory, Kinestethic, Media Audio Visual, hasil belajar IPS.